A Case History Investigation of Two Coal Bumps in the Southern Appalachian Coalfield - David Newman (International Conference on Ground Control in Mining, 2002)
The Southern Appalachian coalfield has a long history of coal bumps that are attributable to a unique combination of topography, geology, and multiple seam mining. The high pillar stresses that generate a coal bump result from: i. mountainous topography where the overburden commonly exceeds 1,500 feet beneath ridges, ii. multiple seam mining, iii. thin interburden between active and abandoned mines, iv. thick beds of competent sandstone and sandy shale strata throughout the stratigraphic section, v. strong coal seams, and vi. irregular pillar and mining geometry in older room-and¬pillar mines. Coal has been intensively mined for more than 100 years in Eastern Kentucky, Southwestern Virginia, and Southern West Virginia. As a result, it is commonplace to have abandoned mines above and/or below active operations. Therefore, those conditions that generate coal bumps will be more prevalent in the future, as underground mining continues in Southern Appalachia. The focus of this paper concerns two coal bumps that occurred in the Kellioka seam where both undermining and overmining had occurred. The purpose of the investigation is to determine the magnitude and distribution of vertical stress that initiated the bumps, to identify bump-prone areas in the unmined reserve, and to recommend pillar centers and mining layouts to avoid future bumps. The state of stress in three vertically adjacent seams was examined using the LAMODEL boundary element program. Large, detailed numerical models were constructed of both bump areas and of the remaining unmined reserve block. The results of the numerical analyses were compared with those obtained using analytical equations.